2018
DOI: 10.3389/fimmu.2018.02935
|View full text |Cite
|
Sign up to set email alerts
|

Clara Cell 10 kDa Protein Alleviates Murine Hepatitis Virus Strain 3-Induced Fulminant Hepatitis by Inhibiting Fibrinogen-Like Protein 2 Expression

Abstract: Background: Fulminant hepatitis (FH) is a serious threat to human life, accompanied by massive and rapid necroinflammation. Kupffer cells, the major immune cell population involved in innate immune responses, are considered to be central for FH. Fibrinogen-like protein 2 (Fgl2) is a pro-coagulant protein that is substantially induced in macrophages upon viral infection, and Fgl2 depletion represses murine hepatitis virus strain 3 (MHV-3) infection. Clara cell 10 kDa (CC10) protein is a secretory protein with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…mFgl2 mediates macrophage activation 18 , cell adhesion, trans-endothelial migration 19 and tumor growth 20 while sFgl2 inhibits the proliferation of effector T cells 21 and maintains the immunosuppressive activity of Tregs 22 . Previous work from our group indicated that interference with fgl2 expression significantly increased the survival rate and alleviated liver injury in a murine model of fulminant hepatic failure 23 , 24 . Furthermore, mfgl2 is directly related to the progression of hepatic inflammation in patients with severe hepatitis B 25 .…”
Section: Introductionmentioning
confidence: 87%
“…mFgl2 mediates macrophage activation 18 , cell adhesion, trans-endothelial migration 19 and tumor growth 20 while sFgl2 inhibits the proliferation of effector T cells 21 and maintains the immunosuppressive activity of Tregs 22 . Previous work from our group indicated that interference with fgl2 expression significantly increased the survival rate and alleviated liver injury in a murine model of fulminant hepatic failure 23 , 24 . Furthermore, mfgl2 is directly related to the progression of hepatic inflammation in patients with severe hepatitis B 25 .…”
Section: Introductionmentioning
confidence: 87%
“…Group 1 was transfected with NC small interfering RNA (siRNA). Group 2 was transfected with NC-siRNA and exposed to 1,000 PFUs of MHV-3 for 4 h (Yu et al 2018 ). Group 3 was exposed to PQQ (0.1 μM) for 6 h, transfected with NC-siRNA, and exposed to 1,000 PFUs of MHV-3 for 4 h. Group 4 was exposed to PQQ (0.1 μM) for 6 h, transfected with Nrf2-siRNA, and exposed to 1,000 PFUs of MHV-3 for 4 h. All transfection experiments were performed using Lipofectamine 2000 (#11668027; Thermo Fisher Scientific) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%